2015
DOI: 10.1260/0263-0923.34.4.475
|View full text |Cite
|
Sign up to set email alerts
|

Active Off-Road Seat Suspension System Using Intelligent Active Force Control

Abstract: Transmitted vibration from vehicles to driver body generates some problems in the long term. Passive and active seat suspensions are used in heavy duty vehicles to reduce unwanted vibration and prevent health problems due to oscillation. Seat suspension must minimize the driver's body displacement and acceleration to increase riding convenience. Active force control (AFC) method is a new technique which is used in active controllers and makes them more accurate. Therefore, this work represents the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Recently, the AFC was utilized in the active suspension system to ensure the passenger ride and car stability [107]. Hence, the active force control method was proposed by [108] to increase the robustness of the active seat suspension. The artificial neural network (ANN) was used to approximately estimate the seat and human body weight.…”
Section: Other Control Techniquesmentioning
confidence: 99%
“…Recently, the AFC was utilized in the active suspension system to ensure the passenger ride and car stability [107]. Hence, the active force control method was proposed by [108] to increase the robustness of the active seat suspension. The artificial neural network (ANN) was used to approximately estimate the seat and human body weight.…”
Section: Other Control Techniquesmentioning
confidence: 99%
“…Choi and Han [9] and Bae and Kang [16] have studied the seat suspension with the human model without considering the vehicle suspension model. Gohari and Tahmasebi [17] implemented the active control on the seat suspension while analysing the performance with various road disturbances, but only the seat suspension was considered. Swethamarai and Lakshmi [18] implemented a Fuzzy-PID controller for the quarter car active suspension system with 3-DOF and reported that the Fuzzy-PID control reduced the driver's body acceleration better than Fuzzy and PID controls, thus improving the ride comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Author [10] had implemented active force control (AFC) technique to actively control the seat suspension of heavy duty vehicles. AFC is integrated with ANN to estimate the mass of driver and seat.…”
Section: Introductionmentioning
confidence: 99%